Dynamic Characteristics of Medical and Demographic Indicators of Public Health in Arkhangelsk Oblast in the First Twenty Years of the XXI Century: Retrospective Analytical Descriptive Study - K. V. Shelygin; Yu. A. Sumarokov (Кубанский научный медицинский вестник, 2023)
Background. Assessing the dynamic characteristics of basic public health indicators is essential to ensure the sustainable human development, quality of life and health care system performance in the Arctic and Subarctic regions of Russia. The study is based on the need for constant monitoring of the medical and demographic situation in order to provide timely correction of measures for improving the health care system performance.Objective — to assess the trends in basic medical and demographic indicators characterizing the population health of the Arkhangelsk Oblast. Target population: population of the Arkhangelsk Oblast, no impacts, no outcomes.Methods. Criteria for sample or group formation: the research was performed by means of a continuous method based on the study of population of medical and demographic events. The main inclusion criterion was the availability of information about a medical and demographic event in the Arkhangelsk Oblast in the Russian Fertility and Mortality database (RusFMD), the database of the Federal State Statistics Service (Rosstat). Estimated parameters: life expectancy, infant mortality, disability, morbidity, natural population growth and chronicity rates related to the population of the Arkhangelsk Oblast excluding the Nenets Autonomous Okrug. The study was conducted between 2021 and 2022. The following measurement methods were used: autoregressive and integrated moving average, Irwin method to identify abnormal values, linear regression, time series dynamics, and method of chain substitutions. The research was performed by means of a continuous method based on studying the population of medical and demographic events.Results. Natural population growth and chronicity rates showed a stable negative trend, which indicated a decrease in the reproduction potential of the population, and an increase in chronic forms of diseases. Life expectancy, primary morbidity, and primary disability demonstrated a positive trend, but with a tendency to exhaust the positive potential. Infant mortality was the only indicator that consistently showed a positive trend. No additional results of the research were reported.Conclusion. The results of the study demonstrated the deterioration in population health of the Arkhangelsk Oblast, which may be due to a decline in living standards and quality of life as well as to a decrease in health care system performance and a rise in its dysfunctionality. The study has no limitations.